Robert Ryman - Colaizzi, Vittorio (New York : Phaidon, 2017)
The only comprehensive monograph on the artist whose abstract 'white' paintings have inspired generations. A much-revered figure in the art world, Robert Ryman has, over six decades, continuously and methodically experimented with the different possibilities inherent within a painting -- abolishing colour in order to focus on material, brushstroke, support, and scale. This, the only comprehensive monograph covering his career to date, places his famous square 'white' paintings with lesser-known but increasingly exhibited works, in order to show that he is not a reductionist, but in fact a restless experimenter.
Introduction: the seeing of painting -- A one-time thing -- Not exactly Expressionist -- Projecting a different experience -- Crazy paintings -- A picture of a line -- Getting the paint across -- The way it acts -- A question of what.
boek
Keywords: Ryman, Robert, -- 1930- -- Criticism and interpretation; Monochrome painting -- United States -- 20th century; Painting, American -- 20th century; Painting, American -- 21st century; Ryman, Robert, -- 1930-; United States; 1900-1999; Criticism, interpretation, etc